2007
DOI: 10.1136/bjo.2006.113134
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pupillary dilatation on glaucoma assessments using optical coherence tomography

Abstract: Aims: To examine the effect of pupillary dilatation on the reliability of retinal nerve fibre layer (RNFL) and optic nerve head (ONH) assessments using Stratus OCT in a glaucoma clinic. Methods: Observational study of 38 patients attending a glaucoma clinic. The ''fast optic disc'' and ''fast RNFL thickness'' programs on Stratus OCT were used to measure the RNFL thickness and ONH cup to disc ratio (CDR). Two scans were done before dilatation and two after dilatation with tropicamide 1% drops. The mean values a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 16 publications
1
26
0
4
Order By: Relevance
“…In a study involving 38 glaucoma patients with a mean age similar to that in our own sample, Smith et al 28 reported that in almost a quarter of cases (23.7%) it was not possible to acquire high-quality OCT images without pupil dilation and that dilated scans were more reproducible and gave different RNFL thickness mean values. A significant effect of pupil dilation was found also by Paunescu et al 29 In a previous study on a group of patients undergoing cataract surgery, our group reported that pupil dilation slightly affected RNFL thickness measurements by Stratus OCT, as RNFL thickness values were statistically higher in the 3601 average measurement and in the nasal quadrant and some differences were found in the other quadrants as well, although statistical difference was not reached.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study involving 38 glaucoma patients with a mean age similar to that in our own sample, Smith et al 28 reported that in almost a quarter of cases (23.7%) it was not possible to acquire high-quality OCT images without pupil dilation and that dilated scans were more reproducible and gave different RNFL thickness mean values. A significant effect of pupil dilation was found also by Paunescu et al 29 In a previous study on a group of patients undergoing cataract surgery, our group reported that pupil dilation slightly affected RNFL thickness measurements by Stratus OCT, as RNFL thickness values were statistically higher in the 3601 average measurement and in the nasal quadrant and some differences were found in the other quadrants as well, although statistical difference was not reached.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21][22] Recently, mydriasis was also induced using Stratus OCT. 20,[23][24][25] Some controversy, in fact, still exists regarding the effect of pupil dilation on RNFL thickness measurements by Stratus OCT: whereas some articles reported that the difference is little or even not statistically significant, 26,27 other studies found that measurements before and after dilation are not interchangeable. 28,29 Being able to acquire OCT scans without mydriasis would allow the operator to save time in a busy practice, would eliminate the risk of angle closure in predisposed eyes, and would not cause annoying visual disturbances in patients undergoing the examination. Moreover, it should be considered that during the follow-up it may occur that the same eye is examined sometimes with and without mydriasis.…”
Section: Introductionmentioning
confidence: 99%
“…14-18 Although SD-OCT has shown better reproducibility than TD-OCT, 18,19 glaucoma discrimination has been found to be similar for TD-OCT and SD-OCT. 20 Several studies have investigated the influence of pupil dilation on RNFL measurements obtained with TD-OCT. [11][12][13]21,22 Smith et al 11 suggested that the TD-OCT requires pupil dilatation to perform the examination, as the quality of scans and the reproducibility of RNFL measurements is not satisfactory in 25% of undilated AT, average thickness; IT, inferior thickness; NT, nasal thickness; ST, superior thickness; SD-standard deviation; TT, temporal thickness; Q, quality score; H1T to H12T, thickness at 0100, 0200, 0300, 0400, 0500, 0600, 0700, 0800, 0900, 1000, 1100, and 1200 hours sectors. a Comparison between non-dilated glaucoma group vs non-dilated healthy individuals.…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10] Recently, advances in technology allowed the development of spectral-domain OCT (SD-OCT), which provides faster acquisition, better resolution, and improved visualization of retinal morphology. 8 By using the advanced technology of SD-OCT, the Cirrus HD-OCT acquires data about 70 times faster (27 000 vs 400 A-scans per second) and with better resolution (5 vs B10 mm of axial resolution in tissue) when compared to the first generation of OCT. 9,11 Furthermore, some studies have indicated that time-domain OCT requires pupil dilation for the acquisition of good quality images of the retina and RNFL. [11][12][13] Although the manufacturer of the Cirrus HD-OCT indicates that the images can be obtained without pupil dilation, there is no study in the literature investigating the effects of pupil dilation on the measurements obtained with this instrument.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation